Tobacco Research Publications: Global Scenario - Suryanarayana, Y. V. (Journal of Information and Knowledge, 2002)
Tobacco research is published in various journals throughout the world. All these are scanned and abstracted in abstracting periodicals viz. TOBACCO ABSTRACtS and CORESTA INFORMATION BULLETINS. CORESTA brings out their bulletins in CD-ROM form also since 1975. The CD-ROM was analysed for different aspects of tobacco publications of Indian and other countries contributions. The growth and fall of. tobacco literature in the world and also in India in different disdplines is discussed in detail. Publications in different languages are also given. Lastly concludes that from 1987 onwards the research publications has decreased in the world as wei. as in India.